The Multi-Ocean Distribution of the Hadal Amphipod, Hirondellea dubiaDahl, 1959 (Crustacea, Amphipoda) - Weston, Johanna N. J.; Jamieson, Alan J. (Frontiers in Marine Science, 2022)
The hadal zone (depths > 6000 m) comprises isolated features that host high degrees of endemism, with species inhabiting only a single feature or a group of adjacent features. The amphipod, Hirondellea dubia Dahl, 1959, is an abundant scavenger at the hadal depths of the Kermadec, Tonga, and New Hebrides trenches in the Southwest Pacific Ocean, particularly at depths > 9500 m. However, several records have hinted that H. dubia may not be restricted to the Southwest Pacific nor be exclusively hadal. Here, we present new records of H. dubia recovered by baited landers deployed to five hadal trenches during three expeditions and assess the geographic and vertical distribution of this species. To rule out the possibility of cryptic diversity, morphological taxonomy was paired with two mitochondrial markers (16S and COI) to test for species boundaries among the new and published molecular data using four delineation approaches (ABGD, CD-HIT, GMYC, and bPTP). We found H. dubia to be a single species and not restricted to the Southwest Pacific or hadal depths. This species’ geographic range extends from the Southwest Pacific to the Mariana Trench (Northwest Pacific), the Clarion-Clipperton Zone (Central Pacific), the South Sandwich Trench (Southern), and the Puerto Rico Trench (North Atlantic). This amphipod’s vertical range spans over half of the ocean’s total depth, between 4700 m to 10,817 m. This study presents an extraordinary geographic range extension to a species long considered endemic to a cluster of three Southwest Pacific trenches and shows a pan-oceanic distribution across extremely isolated hadal features.